Deciphering Controls of Pore‐Pressure Evolution on Sediment Bed Erosion by Debris Flows - Hongchao Zheng; Xinli Hu; Zhenming Shi; Danyi Shen; Tjalling De Haas (Geophysical Research Letters, 2024)
Abstract Pore‐fluid pressure (PP) plays an important role in bed erosion, but the mechanisms that control PP evolution and the resulting feedbacks on flow dynamics are unclear. Here, we develop a general formulation, allowing quantification of the propensity for PP evolution of saturated and unsaturated bed sediments. We conduct erosion experiments by systematically varying grain composition and water content of beds, for investigating effects of PP evolution on flow erosion. With increasing water content, PP shows a slight rise in deforming beds with drained behavior but significant larger rise in undrained beds. Regardless of bed composition, the erosion rate of beds presents a synchronous change tendency with PP evolution due to the loss in basal friction. PP instigates positive feedback that induces a remarkable gain of flow velocity and momentum on wet beds with undrained behavior. Our results help explain observations of volume growth and long run out of debris flows.